Tumor Ki-67, ER and PR, and antibodies against estradiol and progesterone in breast cancer patients - A. N. Glushkov; E. G. Polenok; S. A. Mun; L. A. Gordeeva; M. V. Kostyanko; A. V. Antonov; P. V. Bayramov; N. E. Verzhbitskaya; G. I. Kolpinskiy (Фундаментальная и клиническая медицина, 2023)
Aim. To investigate the associations of cell proliferation marker Ki-67 in estrogen receptor (ER) and progesterone receptor (PR) positive (ER+/ PR+) and negative (ER-/PR-) tumors with the ratio of antibodies against estradiol and progesterone (IgA1-E2/IgA1-Pg) in the serum of breast cancer (BC) patients.Materials and Methods. Antibodies against steroid hormones were analyzed by ELISA in the serum of 432 healthy women and 1212 patients with BC (573 patients with I stage and 639 patients with II–IV stages). Expression of Ki-67, ER and PR in tumors was determined by immunohistochemical staining. Serum estradiol and progesterone were measured by enzyme-linked immunosorbent assay.Results. In total, low IgA1-E2/IgA1-Pg (≤ 1) and high IgA1-E2/IgA1-Pg (> 1) ratio were revealed in 49.3% and 50.7% of healthy women; in 25.7% and 74.3% of stage I BC patients with tumor Ki-67 < 14 (р < 0.001; OR = 0.4 and OR = 2.8, respectively), and in 17.1% and 82.9% of stage I BC patients with tumor Ki-67 > 30 (р < 0.001; OR = 0.2 and OR = 4.7, respectively). The differences between patients with low and high tumor Ki-67 levels in relation to low and high IgA1-E2/IgA1-Pg ratio were statistically significant (p = 0.03). In stage I BC patients with ER+/PR+ and tumors with Ki-67 < 14, low and high IgA1-E2/IgA1-Pg ratio were found in 25.0% and 75.0% cases (р < 0.001; OR = 0.3 and OR = 2.9, respectively). In stage I BC patients with ER+/PR+ and tumors with Ki-67 > 30, low and high IgA1-E2/IgA1-Pg ratio were found in 12.9% and 87.1% cases (р < 0.001; OR = 0.2 and OR = 6.6, respectively). In patients with ER+/PR+ tumors, the differences between patients with low and high tumor Ki-67 levels in relation to low and high IgA1-E2/IgA1-Pg ratio were also statistically significant (p = 0.009). In patients with ER-/PR- tumors, the differences between patients with low and high Ki-67 levels in relation to low and high IgA1-E2/IgA1-Pg ratio were not revealed. The proportion of breast cancer patients with tumor Ki-67 > 30 increased from I to II–IV BC stages regardless of IgA1-E2/IgA1-Pg ratio.Conclusion. IgA1-E2/IgA1-Pg ratio may serve as a predictor of tumor proliferative activity in stage I BC patients with ER+/PR+ tumors.